Phenotypic trajectories during the evolution of hybrid lineages : the case of Oophaga histrionica and Oophaga lehmanni (2017)
"Phenotypic variation is common on an inter- and intraspecific level among poison frogs (Dendrobatidae) and is the starting point for selective and non-selective forces to act upon. Hybridization between two species can result in an increase of the initial phenotypic variation, even though it is believed to act homogenizing rather than to differentiate phenotypic traits. It might allow for novel combinations of characters to emerge, allowing organisms to explore new peaks in the fitness landscape. While hybridization is more common than previously thought, and might in rare cases even lead to speciation, it is still largely unknown how multi-trait phenotypes of hybrid lineages evolve from the very moment of introgression when the hybrid lineages persist over time. In this study we measured advertisment calls, coloration patterns, the diet and degree of dietary specialisation of O.histrionica and O.lehmanni as well as two hybrid lineages (recent and old) and tested (1) whether these traits were intermediate between the parental lineages, resembled more one of them, or, alternatively, if new phenotypes arose; and (2) whether these traits concomitantly changed across time or, alternatively, if some traits changed more than others." -- Tomado del Formato de Documento de Grado.